The impact of persistent poor housing conditions on mental health: A longitudinal population-based study - Pevalin, David J.; Reeves, Aaron; Baker, Emma; Bentley, Rebecca (Preventive medicine, 2017)
Living with housing problems increases the risk of mental ill health. Housing problems tend to persist over time but little is known about the mental health consequences of living with persistent housing problems. We investigated if persistence of poor housing affects mental health over and above the effect of current housing conditions. We used data from 13 annual waves of the British Household Panel Survey (1996 to 2008) (81,745 person/year observations from 16,234 individuals) and measured the persistence of housing problems by the number of years in the previous four that a household experienced housing problems. OLS regression models and lagged-change regression models were used to estimate the effects of past and current housing conditions on mental health, as measured by the General Health Questionnaire. Interaction terms tested if tenure type modified the impact of persistent poor housing on mental health. In fully adjusted models, mental health worsened as the persistence of housing problems increased. Adjustment for current housing conditions attenuated, but did not explain, the findings. Tenure type moderated the effects of persistent poor housing on mental health, suggesting that those who own their homes outright and those who live in social housing are most negatively affected. Persistence of poor housing was predictive of worse mental health, irrespective of current housing conditions, which added to the weight of evidence that demonstrates that living in poor quality housing for extended periods of time has negative consequences for mental health. •Persistent housing problems in the past are associated with poor mental health.•Long-term change in housing problems and mental health are also correlated.•Social renters and outright owners are affected by housing problems the most.•Both moving out of poor quality housing and removing housing problems improve mental health.•Mental health policy may be less effective if it does not consider housing quality.